2012
DOI: 10.3961/jpmph.2012.45.6.381
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cigarette Smoking and Muscle Strength in Japanese Men

Abstract: ObjectivesTo investigate the link between cigarette smoking and muscle strength in Japanese men.MethodsWe used data on 4249 Japanese men, aged 43.3±13.9 years, in this cross-sectional investigation study. Grip strength and leg strength were measured as indicators of overall muscle strength. Meanwhile, subjects' cigarette smoking habits were recorded by trained medical staff. The effect of cigarette smoking on muscle strength was evaluated.ResultsA total of 1618 men (38.1%) were smokers and 1481 men (34.9%) exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 8 publications
3
32
4
1
Order By: Relevance
“…The relationship between cigarette smoking and muscle strength has been studied previously. Research showed that tobacco smoke inhalation affects muscle flexibility and strength in healthy adults or athletes, as well as grip strength [37][38][39]. In our study, total 9 (5 in nonsmoking group and 4 in smoking group) patients developed reduced muscle strength at the final follow-up, however, there were no difference between both groups.…”
Section: Discussioncontrasting
confidence: 43%
“…The relationship between cigarette smoking and muscle strength has been studied previously. Research showed that tobacco smoke inhalation affects muscle flexibility and strength in healthy adults or athletes, as well as grip strength [37][38][39]. In our study, total 9 (5 in nonsmoking group and 4 in smoking group) patients developed reduced muscle strength at the final follow-up, however, there were no difference between both groups.…”
Section: Discussioncontrasting
confidence: 43%
“…Sedentary physical activity would induce the functional decline of subjects and cigarette smoking accelerates changes in organic functions. In fact, lower aerobic exercise level, muscle strength and flexibility were characteristic features in subjects with cigarette smoking [5][6][7]. These many possible factors may affect one leg with eyes closed balance in this study.…”
Section: Discussionmentioning
confidence: 59%
“…height, body weight, body mass index (BMI), abdominal circumference and hip circumference, the data on cigarette smoking [6,7,10], exercise habits [11] and one leg with eyes closed balance [12] were also evaluated.…”
Section: Clinical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Também foi observado achado semelhante no estudo norte-americano de Woods et al (2005) Não foi encontrada associação entre presença de tabagismo e os componentes do fenótipo no presente estudo, divergindo de estudos anteriores que relatam forte associação, principalmente, com a redução da força de preensão palmar (AL-OBAIDI; AL-SAYEGH; NADAR, 2014;SAITO et al, 2012) e perda de peso (HANG et al, 2017;CHO et al, 2017). (TRIBESS, 2012).…”
Section: Procedimentos Estatísticosunclassified